The Effect Of Using XCAST Based Routing Protocol in Wireless Ad Hoc Networks. - Alzyoud, Faisal Y.; Tat, Chee Wan (2009)
Wireless ad hoc networks are a type of wireless network that can be easily created without the need of network infrastructure or central administration.